Transluminal endoscopic necrosectomy after acute pancreatitis: a multicentre study with long-term follow-up (the GEPARD Study). Issue 9 (11th March 2009) - Seifert, H; Biermer, M; Schmitt, W; Jürgensen, C; Will, U; Gerlach, R; Kreitmair, C; Meining, A; Wehrmann, T; Rösch, T
Abstract : Background: As with endoscopic transmural drainage of peripancreatic fluid collections, the same transluminal access can be expanded to introduce an endoscope through the gastrointestinal wall into the retroperitoneum and remove infected pancreatic necroses under direct visual control. This study reports the first large series with long-term follow-up. Methods: Data for all patients undergoing transluminal endoscopic removal of (peri)pancreatic necroses between 1999 and 2005 in six different centres were collected retrospectively, and the patients were followed up prospectively until 2008. The initial patient and treatment outcome data were recorded, as were long-term results. Results: Ninety-three patients (63 men, 30 women; mean age 57 years) underwent a mean of six interventions starting at a mean of 43 days after an attack of severe acute pancreatitis. After establishment of transluminal access to the necrotic cavity and subsequent endoscopic necrosectomy, initial clinical success was obtained in 80% of the patients, with a 26% complication and a 7.5% mortality rate at 30 days. After a mean follow-up period of 43 months, 84% of the initially successfully treated patients had sustained clinical improvement, with 10% receiving further endoscopic and 4% receiving surgical treatment for recurrent cavities; 16% suffered recurrent pancreatitis. Conclusions: Direct transluminal endoscopic removal of pancreatic necroses is associated with good long-term maintenance of the high initial efficacy; complications can occur, with an associated mortality of around 7.5%. Further studies are necessary in order to optimise endotherapy and define its role in relation to surgery in the clinical management of such patients.